1999
DOI: 10.1007/pl00009597
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dysphagia with the Use of Pulse Oximetry

Abstract: Recent anecdotal literature has shown a relation between arterial oxygen saturation (SpO2), as measured by pulse oximetry, and aspiration during eating. The present study was designed to determine whether bedside pulse oximetry has a role in the assessment of pharyngeal phase dysphagia. Forty-six adult patients with clinically suspected swallowing abnormalities underwent modified barium swallow to evaluate dysphagia. After determining baseline oxygen saturation by pulse oximetry, different consistencies of bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 11 publications
1
49
0
5
Order By: Relevance
“…In contrast to previous reports, [3][4][5][6][7][8][9][10][11] this study is in agreement with those investigations that showed that pulse oximetry was not a reliable method for detecting aspiration risk. [12][13][14] The study also showed that neither the modified BSA nor pulse oximetry, whether used alone or in combination, had adequate sensitivity, specificity, or predictive value for identifying the presence or absence of aspiration as seen on VF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast to previous reports, [3][4][5][6][7][8][9][10][11] this study is in agreement with those investigations that showed that pulse oximetry was not a reliable method for detecting aspiration risk. [12][13][14] The study also showed that neither the modified BSA nor pulse oximetry, whether used alone or in combination, had adequate sensitivity, specificity, or predictive value for identifying the presence or absence of aspiration as seen on VF.…”
Section: Discussionsupporting
confidence: 89%
“…2 There is considerable debate on the role of pulse oximetry as a bedside test to evaluate aspiration risk. The findings of an association between desaturation and aspiration [3][4][5][6][7][8][9][10][11] have not been consistently replicated in the literature. Three recent studies were unable to demonstrate a clear relation between desaturation during feeding and aspiration, [12][13][14] whereas other studies found some association, but with a wide range of sensitivity and specificity values on comparison with VF or FEES.…”
mentioning
confidence: 99%
“…Perhaps this also indicates that measuring oxygen saturation levels to determine aspiration in the context of dysphagia, aging, and changing respiratory patterns needs further investigation. Sherman et al [18] discussed some of the reasons for the diculties in using oxygen desaturation from pulse oximetry to indicate aspiration, including patients with concomitant illnesses aecting oxygen saturation, the eect of dierent substances when aspirated, and the dierent sensitivity of oxygen saturation at dierent arterial oxygen partial pressures.…”
Section: Oxygen Saturationmentioning
confidence: 99%
“…42,43 Zaidi et al 40 subsequently found greater desaturation after swallowing water in acute stroke patients than in matched control subjects, and the degree of desaturation correlated with clinical assessment of aspiration risk, although statistical criticisms have been leveled at their analyses. 44 Sherman et al 45 performed pulse oximetry during VF and demonstrated significant desaturation in patients who suffered aspiration of material or penetration without clearing compared with those in whom penetration occurred with clearing or not at all, but patient numbers were small and age was very variable. Some studies have found no clear relationship between desaturation and aspiration, 44,46 but 1 study demonstrated persistently lower saturations in aspirators than nonaspirators.…”
Section: Pulse Oximetrymentioning
confidence: 99%